Integration of Legalization Information System Web-Based using Shipping API and Telegram API - Sucipto Sucipto; Jamilah Karaman (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2020)
Education is a right for every citizen. Quality education makes people more intelligent. Educational outcomes documented in a file called a diploma. A diploma is a necessary file for doing things related to work or other administrative matters. Generally, the diploma file submitted is in the form of a photocopy of a certificate that has been legalized for administrative requirements. The process of legalizing diplomas is often a hindrance because the time required is quite long and especially if someone is in an area far from where to take care of legalization. In the industrial era 4.0, information technology can be utilized to facilitate public access to services in the world of education, for example, using technology to implement an online legalization system. Application of technology in the legalization process is not just online but can be integrated with API (Application Programming Interface). It can attract millennial access to the application easily. There are two APIs used, namely the Shipping API and the Social Messaging API. Shipping API makes it easy to check shipping costs based on alumni location. Social messaging API with assistant features so that it can be easier to serve alumni accessing application features via Telegram. This study aims to facilitate the alumni in legalizing online to make time-efficient and affordable—implementation of information systems with the integrated website media Telegram API and Rajaongkir or shipping cost API. Based on testing the usability testing results obtained a value of 4.56 on a scale of 5. These results indicate that the application can function following the needs of users of information systems.